Breast reconstructions: a 16-year retrospective study - Ognev Meireles Cosac; Amanda Costa Campos; Ronan Caputi Silva Dias; Rafael Sabino Caetano Costa; Suellen Vieira da-Silva; Anderson de Azevedo Damasio; João Pedro Pontes Camara; Jose Carlos Daher (Revista Brasileira de Cirurgia Plástica)
Introduction: Breast cancer is the second most common type of cancer among women in Brazil. An estimated 59,700 new cases of breast cancer were reported in the 2018-2019 biennium. Breast reconstruction is a safe procedure, and various surgical procedures have been described, including conservative techniques and use of neighborhood flaps, alloplastic materials, and pedicled and microsurgical myocutaneous flaps. The objective of this study was to analyze cases of breast reconstruction after mastectomy for breast cancer performed over a period of 16 years. Methods: We reviewed the medical records of patients who underwent breast reconstruction after mastectomy for breast cancer between January 2002 and December 2017. Results: Within the study period, 586 patients underwent breast reconstruction. Breast reconstruction was performed with a transverse rectus abdominis myocutaneous muscle (TRAM) flap in 160 patients, with conservative techniques in 107 patients, with a latissimus dorsi myocutaneous flap (LDMF) in 156 patients, with prostheses in 113 patients, and secondarily in 50 patients. Before October 2007, the proportion of patients who underwent bilateral surgeries with a TRAM flap and LDMF was 30%, and since then, the percentage has increased to 83.3%. One or more types of complications occurred in 203 patients (34.64%) who underwent surgery, with a total of 335 complications . Most outpatient complications did not require surgical reassessment. Conclusion: The incidence of bilateral surgery increased, which is attributed to the increase in the number of prophylactic mastectomies in the contralateral breast and in the number of reconstructions using a LDMF compared with that using a TRAM flap. A significant increase in the number of reconstructions with silicone implants was also observed.